2014
DOI: 10.1016/j.jhin.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

From SARS in 2003 to H1N1 in 2009: lessons learned from Taiwan in preparation for the next pandemic

Abstract: In anticipation of a future pandemic potentially arising from H5N1, H7N9 avian influenza or Middle East Respiratory Syndrome, and in large part in response to severe acute respiratory syndrome (SARS) in 2003, the city of Taipei, Taiwan, has developed extensive new strategies to manage pandemics. These strategies were tested during the 2009 H1N1 outbreak. This article assesses pandemic preparedness in Taipei in the wake of recent pandemic experiences in order to draw lessons relevant to the broader internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 41 publications
2
88
0
12
Order By: Relevance
“…As a result, TCB has been expanded across Taiwan's hospital system and has been deployed in outbreaks that have occurred since then. 30 In addition to the microapplication of TCB to hospitals, TCB has also been applied nationally, drawing on the six regional communicable disease control centers. The network facilitates communication and integrates response efforts (including sharing training and surge capacity) among the national and local level governments while also incorporating input from hospitals, infection control units and local health departments.…”
Section: Stateehospital Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, TCB has been expanded across Taiwan's hospital system and has been deployed in outbreaks that have occurred since then. 30 In addition to the microapplication of TCB to hospitals, TCB has also been applied nationally, drawing on the six regional communicable disease control centers. The network facilitates communication and integrates response efforts (including sharing training and surge capacity) among the national and local level governments while also incorporating input from hospitals, infection control units and local health departments.…”
Section: Stateehospital Cooperationmentioning
confidence: 99%
“…In addition, hotel administrators are required to distribute notices to guests explaining epidemic risks and the various measures to be taken to avoid infection. 30 This same approach has been adopted in other cities across Taiwan. Kaohsiung city government implemented similar collaboration with its hotels when, while hosting the 2009 World Games, the city was struck by the 2009 H1N1 outbreak.…”
Section: Stateeprivate Sector Cooperationmentioning
confidence: 99%
“…After 17 years, physicians in Taiwan face another novel coronavirus outbreak originating in China. 1 With the past experience of severe acute respiratory syndrome (SARS), 2,3 we respond quickly this time. However, a new pathogen inevitably raises new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…2 Fomites are important because while populations generally protect themselves from clearly observable droplet transmissions (coughing, sneezing), being invisible, fomite transmission is regularly overlooked both in hospitals and communities. [3][4][5] Consequently, during the community saturation phase, fomite transmission may play a larger role than droplet transmission as a mechanism in emergent infectious diseases. [3][4][5][6] In this paper we argue that by implementing enhanced Traffic Control Bundling (eTCB), 6 to transmission by the index case via droplets and contact with exposed people in the same care zone.…”
mentioning
confidence: 99%
“…[3][4][5] Consequently, during the community saturation phase, fomite transmission may play a larger role than droplet transmission as a mechanism in emergent infectious diseases. [3][4][5][6] In this paper we argue that by implementing enhanced Traffic Control Bundling (eTCB), 6 to transmission by the index case via droplets and contact with exposed people in the same care zone. However, later analysis found that those without contact history with the index case were likely infected by fomites on bed curtains and/or public restroom fixtures touched by the index case who had been suffering from walking pneumonia and diarrhea.…”
mentioning
confidence: 99%